Nano-Engineering for Precision Oncology Unraveling Molecular Mechanisms and Pioneering Revolutionary Cancer Therapies - Liaqat, Ayesha; Mohsin Saleem Ghouri, Mohsin Saleem; Shehzadi, Raheela; Munir, Rida; Bashir, Mehwish; Rehmat, Ali; Bashir, Malka Saba; Irshad, Muhammad; Ahmed, Haseeb (Indus Journal of Bioscience Research, 2025)
With previously unheard-of improvements in cancer detection, therapy, and monitoring, nano-engineering has become a game-changer in precision oncology. Researchers can create nanoscale drug delivery systems that maximize therapeutic efficacy and reduce systemic toxicity by utilizing nanotechnology. With an emphasis on targeted drug delivery, tumor microenvironment manipulation, and nanocarrier-mediated immunotherapy, this study investigates the molecular processes underlying nano-engineered therapeutics. By increasing specificity and lowering side effects, innovations including photothermal and photodynamic therapy, biomimetic nanostructures, and nanoparticle-based CRISPR gene editing are transforming the treatment of cancer. Furthermore, real-time, non-invasive cancer detection and monitoring are made possible by liquid biopsy technologies and nano-biosensors, allowing for early intervention and individualized treatment plans. A comprehensive approach to cancer management is provided by the interaction of nanotechnology and molecular oncology, which also makes it easier to create multipurpose nanoplatforms that combine diagnosis and treatment (theranostics). Nano-engineering has enormous promise to overcome drug resistance, improve immune system engagement, and enable precision-targeted treatments as precision oncology develops. To enable clinical translation, however, issues including biocompatibility, large-scale production, and regulatory permissions need to be resolved. With a focus on its role in developing ground-breaking cancer treatments and changing the face of precision oncology, this study focuses on recent advances, present difficulties, and potential future paths in nano-engineering for cancer therapy.